Methodology for determining the amount of ferrite and pearlite in cast iron using standard computer image processing programs - A. I. Pokrovsky (Литьë и металлургия)
Standard GOST 3443–87 used in metallurgical practice does not permit an accurate quantitative assessment of the content of pearlite and ferrite in the structure of cast iron while specialized software for computer image analysis is rather expensive, are not available to all enterprises and, moreover, require highly qualified staff.In this work, a new, simple technique is proposed for determining the amount of ferrite and pearlite in cast iron using a special etchant that provides a high-contrast image, and standard computer image processing programs, which permit obtaining a grayscale histogram where the shades of gray vary from black to white in the range from 0 to 255. Then, an additional binarization is performed to convert the image into black and white only. In the resulting histogram, the height of black peaks is directly proportional to the content of perlite in combination with graphite, while that of white peaks is proportional to the content of ferrite. The amount of graphite inclusions preliminarily determined on the unetched metallographic section permits determining the exact ratio of pearlite and ferrite in the alloy.